Structural optimization of the telescopic arm of a container spreader based on finite element analysis - Er, Zhi Wee (2018)
Container spreader is used to lift standard shipping containers. The telescopic arm is an integral part of the spreader that adapts to different container sizes. This project aims to analyze the structural strength and stability of the existing telescopic arm, and to improve the telescopic arm into a lightweight design with a higher buckling strength. A simplified finite element model of the existing telescopic arm is created by using computer-aided design software. The structural strength and stability of the model are analyzed by using finite element analysis software based on the working condition of the telescopic arm as defined in BS2573-1 standard. The analysis results are used to determine the minimum structural factor of safety, buckling load factor and buckling mode shapes of the telescopic arm. These results (designated as a reference) are used to improve the existing telescopic arm into a light weight design with higher structural and buckling strength. New telescopic arm designs as well as potential improvements to the existing design are proposed in this thesis. Finite element analyses are conducted on the designs and results are compared against the reference (based on existing design). The comparisons show improvements over the existing telescopic arm design. The various pros and cons of all the new and improved telescopic arm designs are also discussed in this thesis. In summary, the existing telescopic arm is successfully analyzed, redesigned and optimized. Suggestions of further improvements are also included.